Identification of Naturally Occurring Carbazole Alkaloids Isolated from Murraya koenigii and Glycosmis pentaphylla by the Preparation of HPLC Fingerprint - Chakraborty, M. (Journal of Scientific Research, 2022)
The plants Murraya koenigii and Glycosmis pentaphylla are rich sources of different carbazole alkaloids. A number of monomeric carbazole alkaloids with C13, C18, and C23 carbon frames and a good number of dimeric carbazole alkaloids were isolated from these two plants. Scientists are still working on these two plants in search of more and more novel compounds. Many of these alkaloids have potential biological activities. Scientists have determined the structures of these compounds by detailed analysis of spectral data like UV, IR, Mass,1H NMR, and 13C NMR (1D and 2D). These procedures require expertise in spectral data analysis and huge time, and also these instruments are very costly. In this paper, I report the preparation of the HPLC fingerprint of some known carbazole alkaloids. These HPLC data will be helpful in quick and unambiguous identification of the natural products.